Antithrombotic therapy following revascularization for chronic limb-threatening ischaemia: a European survey from the ESC Working Group on Aorta and Peripheral Vascular Diseases. Issue 3 (8th October 2022) - De Carlo, Marco; Schlager, Oliver; Mazzolai, Lucia; Brodmann, Marianne; Espinola-Klein, Christine; Staub, Daniel; Aboyans, Victor; Sillesen, Henrik; Debus, Sebastian; Venermo, Maarit; Belch, Jill; Ferrari, Mauro; et al.
Abstract: Aims: Chronic limb-threatening ischaemia (CLTI) entails dismal outcomes and is an absolute indication to lower extremity revascularization (LER) whenever possible. Antithrombotic therapy is here crucial, but available evidence on best strategies (choice of drugs, combinations, duration) is scarce. We conducted a European internet-based survey on physicians' use of antithrombotic therapy after revascularization for CLTI, under the aegis of the ESC Working Group on Aorta and Peripheral Vascular Disease in collaboration with other European scientific societies involved in CLTI management and agreeing to send the survey to their affiliates. Methods and results: 225 respondents completed the questionnaire. Antithrombotic therapy following surgical/endovascular LER varies widely across countries and specialties, with dedicated protocols reported only by a minority (36%) of respondents. Dual antiplatelet therapy with aspirin and clopidogrel is the preferred choice for surgical (37%) and endovascular (79%) LER. Dual pathway inhibition (DPI) with aspirin and low-dose rivaroxaban is prescribed by 16% of respondents and is tightly related to the availability of reimbursement (OR 6.88; 95% CI 2.60–18.25) and to the choice of clinicians rather than of physicians performing revascularization (OR 2.69; 95% CI 1.10–6.58). A ≥ 6 months-duration of an intense (two-drug) postprocedural antithrombotic regimen is more common among surgeons than among medical specialists (OR 2.08; 95% CI 1.10–3.94). Bleeding risk assessment is not standardised and likely underestimated. Conclusion: Current antithrombotic therapy of CLTI patients undergoing LER remains largely discretional, and prescription of DPI is related to reimbursement policies. An individualised assessment of thrombotic and bleeding risks is largely missing. Graphical Abstract: